Gestión de riesgos en prácticas de campo en docentes de la Facultad de Agronomía, fundo Zungarococha, Loreto, 2024 - Tantalean Monteiro, Samantha Vanessa (2024)
Risk management in field practices is an essential aspect for the safety of teachers and students at the Faculty of Agronomy, especially at the Zungarococha Farm. However, the results show that 61.8% of teachers participate in field activities with their students, many face a lack of institutional support in terms of adequate training and resources for safety and health during their academic practices. Most teachers have average experience in occupational safety, but their active participation in risk management is limited due to insufficient training and lack of safety protocols in teaching workshops. To improve this situation, it is recommended to increase the support of the institution through the implementation of training programs, specific security protocols for each workshop, and the improvement of infrastructure, which will allow more efficient risk management and the protection of the teachers and students in their academic practices.